Answer:
Since the vertex of the parabola is given as (-1, -18), the equation of the parabola can be written in vertex form as:
g(x) = a(x + 1)^2 - 18
where "a" is a coefficient that determines the shape of the parabola. Since the parabola intersects the x-axis at (-4, 0) and (p, 0), we know that these two points are the x-intercepts of the parabola.
To find the value of "p", we need to use the fact that the x-intercepts occur when g(x) = 0. Therefore, we can set the equation of the parabola equal to zero and solve for "x":
a(x + 1)^2 - 18 = 0
Simplifying this equation gives:
a(x + 1)^2 = 18
Since the parabola also intersects the x-axis at the point (-4, 0), we know that when x = -4, g(x) = 0. Substituting this point into the equation of the parabola gives:
a(-4 + 1)^2 - 18 = 0
a(3)^2 = 18
9a = 18
a = 2
Now we can substitute this value of "a" into the equation for the x-intercepts:
2(x + 1)^2 - 18 = 0
x + 1 = ±3
Solving for "x" gives:
x = -1 ± 3
x = -4 or x = 2
Since we know that one of the x-intercepts is at (-4, 0), the other intercept must be at (2, 0). Therefore, the value of "p" is 2.